COMMUNITY PARTICIPATION IN REDUCING MORBIDITY AND MORTALITY RATES FOR TODDLERS AGED LESS THAN 5 YEARS - Pinto, Joaquim (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Community participation plays a central role in reducing morbidity and mortality rates for toddlers younger than 5 years old. This article explores the positive impact of community participation on efforts to prevent and overcome health problems under five. The background of the study reflects the need to detail societal contributions in addressing early childhood health challenges. Despite much previous research on infant health, there are still gaps in knowledge in the context of direct involvement and the effectiveness of community participation. Previous research has highlighted the importance of community empowerment in supporting child health programs, but there is still a lack of understanding of how such participation can be integrated more effectively. The novelty of this study lies in the particular focus on the role of community participation in reducing infant morbidity and mortality. The purpose of this study is to provide deep insight into the contribution of society in designing, implementing, and maintaining toddler health initiatives. The results of this study support the urgency of increasing community participation in efforts to prevent disease and improve the health of toddlers. The benefits of this research are expected to provide practical guidance for policy makers, health practitioners, and related parties to optimize community participation to improve early childhood health